Environmental protection in the digitalization era: new trends and key challenges - Mustafa, Maizatun (On İki Levha Yayincilik A. Ş., 2019)
Environmental law which is becoming an important element within the domestic legal systems of both developed and developing countries continues to evolve in order to respond to constant environmental challenges. However, the current era of digitalization brings about new issues particularly in dealing with critical global problems of climate change and other threats. The relationship between technologies and environmental law is complex. Malaysia as a developing country recognises the role of digital innovation in expanding the boundaries of environmental strategies but it is also cautious of possible harm associated with the misused of technology. This paper presents an overview of the progression of strategies within environmental law in Malaysia for the last 45 years, and discusses the application of technology to support enforcement of the law on various aspects of environmental protection including pollution control, nature conservation and climate change mitigation. The paper concludes that while technologies can possibly bring about conflicting consequences, benefits of new innovations should be identified and utilized as measures to secure environmental targets. In today’s digitalization era, resolutions undertaken to deal with environmental challenges need to be based on transformational measures and the law should thus make allowance for these new trends within its strategies. Qualitative methods of research which include content analysis, and random interviews will be employed to obtain the research output. This paper argues that law which comprehends digital technology potentials can help increase the option of climate change response and enhance the ability to achieve environmental protection objectives. Results from this study are expected to be material sources of reference for the government towards an effective environmental protection in the digitalization era.